(untitled) (Progress Annals: Journal of Progressive Research, 2025)
Foreign language learning is a complex process influenced by a multitude of cognitive, emotional, social, and pedagogical factors. French occupies a significant place among the most widely taught languages in the world due to its history, culture, and international reach. However, despite its appeal, learning French poses numerous challenges for learners. This research aims to analyze the main obstacles encountered when learning foreign languages, with a particular focus on the case of French